Anton Tomaž Linhart Between the German and the Slovenian Language - Strsoglavec, Đurđa (Wydawnictwo Naukowe UAM, 2013)
Anton Tomaž Linhart (1756–1795), is a critical intellectual and scholar of the age of Slo- venian Enlightenment, who introduced causal interpretation of history into Slovenian historiography and started its scientifical philosophy by his historical work Versuch einer Geschichte von Krain und den übrigen Ländern der südlichen Slaven Österreichs (1778, 1791). He was an open-minded man, at first deist under the influence of English philo- sophers, and afterward agnostic under the influence of French materialists and atheists, a man torn between his work as a scholar and a reformer and between the German and the Slovenian language. Linhart’s first works were written in German. Miss Jenny Love(1780) is an attempt of a tragedy, written according to the rules of the Enlightenment period tragedy, exhibiting the contrast between the corrupted nobility and the middle class. The collection of poems Blumen aus Krain für das Jahr 1781 is Linhart’s attempt of contemporary classicist poetry in the rococo fashion and after the manner of the Anacreontic and even Pre-Romantic poetry. Linhart wrote his first Slovenian-language drama Županova Micka (1789), while his second Slovenian drama called Ta veseli dan ali Matiček se ženi(1790) is the most important literary work of the Slovenian Enlightenment and the most wide-ranging echo of the French revolution in the Slovenian lite- rary production of the 18 th century. Linhart’s dramas Županova Micka and Matiček are a manifesto of Slovenehood and democracy expressed in dramatic form, and a declaration of support to the Slovenian people and their struggle against feudalism.
Keywords: Slovenian Enlightenment; Anton Tomaž Linhart; social and functional language stratification; Slovenian historiography